2006
DOI: 10.1097/00006223-200605000-00006
|View full text |Cite
|
Sign up to set email alerts
|

An Interdisciplinary Approach to the Needs of Non-Native-Speaking Nursing Students

Abstract: When some students with English as an additional language did not respond appropriately in the clinical setting, faculty speculated that it was due to lack of proficiency in the English language. Faculty were uncertain of instructional interventions to assist these students. The authors describe how faculty members explored the learning needs of their student population with English as an additional language and offer practical suggestions to help other faculty members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Students should he encouraged to keep vocabulary notebooks or note cards (Brown, 2008;Malu & Figlear, 1998). They can also tape class lectures and listen multiple times (Brown) and make use of lecture outlines or handouts (Caputi, Engelmann, & Stasinopoulos, 2006;Sanner & Wilson, 2008). According to the Cummins model, ESL students may increase their English comprehension by explaining the nursing content they learn in their own language; they should he encouraged to study aloud or present content to family or friends who speak their native language (Abriam-Yago et al, 1999;Choi, 2005).…”
Section: Strategies For Student Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Students should he encouraged to keep vocabulary notebooks or note cards (Brown, 2008;Malu & Figlear, 1998). They can also tape class lectures and listen multiple times (Brown) and make use of lecture outlines or handouts (Caputi, Engelmann, & Stasinopoulos, 2006;Sanner & Wilson, 2008). According to the Cummins model, ESL students may increase their English comprehension by explaining the nursing content they learn in their own language; they should he encouraged to study aloud or present content to family or friends who speak their native language (Abriam-Yago et al, 1999;Choi, 2005).…”
Section: Strategies For Student Successmentioning
confidence: 99%
“…ESL students require extended testing time for reading and processing test items (Caputi et al, 2006;Lujan, 2008;Malu & Figlear, 1998). Abel (2009) also recommended an alternative testing setting for ESL students as a way to reduce anxiety; students struggling to decipher questions will not be surrounded hy classmates who are already completing their tests.…”
Section: Strategies For Student Successmentioning
confidence: 99%
“…Conversation circles are identified as a support for ELLs by Caputi et al (2006). This is when a faculty person meets with a group of ELLs on a periodic basis to discuss the following:…”
Section: Financial Aidmentioning
confidence: 99%
“…In the 1991 study by Memmer and Worth, conversation lab for students to practice English was identified as a support service for ELLs. Conversation circles are identified as a support for ELLs by Caputi et al (2006). This is when a faculty person meets with a group of ELLs on a periodic basis to discuss the following:…”
Section: Additional Practice For Learningmentioning
confidence: 99%
See 1 more Smart Citation